Organizational Contexts for Union Renewal - Yu, Kyoung-Hee (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2014)
SummaryThis article seeks to identify organizational structures and processes that contribute to incorporating immigrant identities and fostering democratic participation in unions. Empirical analysis is based on ethnographic observations conducted in four local branches within the Service Employees International Union (SEIU) of the USA that underwent the Justice for Janitors campaign. Despite the fact that all four local unions experienced external revitalization owing to the campaign, internal renewal was most successful in Los Angeles, least in Washington DC, and somewhat successful in Boston and Houston. For each of the cases, I examine the connection between external dimensions of revitalization—initial mobilizing efforts, bargaining power, and political power—and organizational contexts for renewal—formal and informal structures for participation, and the engagement of immigrant members in union activities. While the union revitalization literature has argued that internal union renewal facilitates external revitalization, how external revitalization affects sustained internal renewal has not yet been examined thoroughly. Most studies examining the relationship between internal and external revitalization have had a relatively narrow window of observation ending typically with successful union recognition; thus, we lacked an understanding of the dynamic relationship between internal and external revitalization over time. The present findings suggest that external revitalization can assist internal renewal. However, building a powerful union did not automatically guarantee democratic participation, and acquiring more economic power through the merging of local unions weakened representational structures. The present results confirm the importance of studying revitalization as a process instead of an outcome, an argument which has been advanced by scholars, yet rarely practiced.